Flash Flood impacts on the life and livelihood of women at haor areas in Bangladesh - Nahar, Najmun; Islam, Shahana; Mahiuddin, Sanjia (National Geographical Journal of India, 2021)
Flash ood is a common disaster in northeastern haor areas of Bangladesh. It frequently affects the life and livelihood of haor people every year. Women are the most vulnerable in this catastrophic situation compared to men. The present study attempted to explore the effects of ash oods on women at Tahirpur Upazila in the Sunamganj district. Asemi-structured questionnaire survey on 172 married women chosen from four villages, seven focus group interviews, and ten key informant interviews was conducted for primary data collection. AFlash Flood Impact Ranking (FFIR) was also prepared to grade the impacts on women based on a 3-points weighted severity scale. The study ndings revealed that women suffered from different diseases with physical injuries and faced many difculties managing the shelter, food, safe water, sanitation, and fuel for cooking during the ood. The FFIR displayed that crop damage, lack of funds, job opportunities, sanitation problems, and food insecurities were the top ve disaster impacts on women. It is suggested that Government and other agencies should increase women's coping strategies by ensuring health services and employment opportunities to mitigate damage and fash flood-related problems.